The Impact Of Primary Hyperhidrosis On Quality Of Life Among Residents In Al-Ahsa City, Saudi Arabia (Journal of Pharmaceutical Negative Results, 2022)
Background: Primary hyperhidrosis is a disease characterized as perspiration more than the body’s physiologic need and can significantly impact one’s occupational, physical, emotional, and social life. However, the prevalence and quality of life of those patients presenting for treatment have not been well studied. Objectives: To determine the prevalence of primary hyperhidrosis and its impact on the quality of life among residents in the Al-Ahsa City of Saudi Arabia. Methods: This is a cross-sectional study conducted in Al-Ahsa City by using structured questionnaires which includes two parts, first part about the subjective diagnosis of hyperhidrosis using “Hyperhidrosis Disease Severity Scale (HDSS)” and the other to assess impairment on quality of life using Amir–de Campos Clinical Protocol for Quality of Life. Results: The study revealed that 18.3% of patients were suffering from barely tolerable or intolerable excessive sweating that is interfering with daily activities indicating a severe degree of HH. A highly statistically significant correlation was found between Amir–de Campos Clinical Protocol for QoL and HDSS among patients in functional and social domain (r = 0.261; p < 0.001), under special circumstances domain (r = 0.336; p <0.001) and overall QoL (r = 0.305; p < 0.001). Conclusions: This study revealed a high prevalence of hyperhidrosis and a significant impact on the quality of life among those affected.